Typification of some names of Graffenrieda (Melastomataceae: Merianieae) - Murillo-Serna, Jhon Steven; Michelangeli, Fabián A.; Alzate-Guarín, Fernando (Phytotaxa, 2019)
In order to provide nomenclature and taxonomic clarity, nine lectotypes are designated for plants currently circumscribed in Graffenrieda. In addition, the typification for some species was analyzed and clarified and we discuss the occurrence of three cases of inadvertent lectotypifications.